Culinary Tourism Development in Palembang City: A Case Study Bebek Gendut Restaurant as An Economic Driver in The Traditional Halal Food - Tiara Suri Handayani; Muhammad Iqbal; Fitria Marisya; Marsinah Marsinah; Despita Despita (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2023)
In writing this report, the writer obtains data from the object research its Bebek Gendut Restaurant Palembang which addressed at Nyoman Ratu street No.1771 Palembang. The purpose of this research is to find out how Bebek Gendut Restaurant serves customers who visit and ensure customers are satisfied with the menu that is served so that it becomes one of the culinary tourism attractions in the city of Palembang. The method used in analysing data is a qualitative method. The results of this research are about the taste of the food, the procedures for promotion, the services used, and the obstacles that often occur during the sales process and how the role Bebek Gendut Restaurant as one of the culinary tourism attractions in the city of Palembang. Bebek Gendut Restaurant quite an important role in the presentation of Javanese cuisine in the city of Palembang, but due to the lack of attention from the management, Bebek Gendut Restaurant not widely known in the city of Palembang. The lack of maintenance and expansion of sales branches is a factor that is less developed culinary industry. This is very influential in increasing revenue turnover and less attractive to visitors.